2013
DOI: 10.1259/dmfr.20130302
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lead apron shielding on absorbed doses from panoramic radiography

Abstract: In conclusion, the results of this study showed no statistically significant differences between a panoramic radiography with or without the use of lead apron shielding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
0
8
0
3
Order By: Relevance
“…Recently, Rottke et al 20 found no statistically significant differences between absorbed organ doses in panoramic examinations with or without the use of lead apron shielding. The opposite was found by Buch et al, 19 who showed that the use of a lead apron in panoramic examinations significantly (72%) reduced the dose to the uterus.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Rottke et al 20 found no statistically significant differences between absorbed organ doses in panoramic examinations with or without the use of lead apron shielding. The opposite was found by Buch et al, 19 who showed that the use of a lead apron in panoramic examinations significantly (72%) reduced the dose to the uterus.…”
Section: Discussionmentioning
confidence: 98%
“…Bei Untersuchungen von Panoramaaufnahmen und dentalen Cone-beam-CT-Bildern zeigten sich keine signifikanten Dosiseinsparungen durch das Tragen einer Patientenschürze [32][33][34].…”
Section: Röntgenaufnahmen In Der Zahnmedizinunclassified
“…A recent paper by Rottke and colleagues [10] found no significant differences in effective dose as assessed in an antropomorphometric phantom by means of thermoluminescence dosimeter (TDL). They concluded that the application of lead aprons Bhas only very little influence, if any, on the doses absorbed during a dental panoramic radiography^ [10]. While TLDs certainly are very useful for assessment of effective dose in such phantoms, their readout accuracy and reproducibility strongly depends on a variety of factors that have to be controlled [11].…”
Section: Introductionmentioning
confidence: 99%
“…For the thyroid, thyroid collars have been found effective for digital panoramic units yet interestingly not for storage phosphor-based systems [9]. A recent paper by Rottke and colleagues [10] found no significant differences in effective dose as assessed in an antropomorphometric phantom by means of thermoluminescence dosimeter (TDL). They concluded that the application of lead aprons Bhas only very little influence, if any, on the doses absorbed during a dental panoramic radiography^ [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation